The Effect of Diversification on Industry Profit Performance in 241 Manufacturing Industries: 1963 - Rhoades, Stephen A. (The Review of Economics and Statistics, 1973)
U NFORTUNATELY, economic theory and existing empirical evidence provide little insight into the effects of diversification on industry performance. This is partially due to the fact that most previous empirical studies of diversification have been concerned with tabulating the extent of,1 or motives for,2 diversification. In order for the antiitrust authorities to develop a rational policy toward conglomerate mergers, it will be necessary to determine the competitive consequences of diversification. This study attempts to provide some empirical evidence on the effects of diversification by examining the relationship between industry price-cost margins and diversification.3 Specifically, the study examines the general proposition that diversification is an element of industry structure and the more narrow hypothesis that diversification raises barriers to entry into an industry. The study is based on a sample of 241 four-digit manufacturing industries from the 1963 Census of Manufactures. The primary testing technique is multivariate regression analysis. Results of the analysis provide tentative support for the proposition 'that diversification has a systematic influence on price-cost margins which may be attributable to certain barriers to entry.